Habitat Conditions Malayan Porcupine (Hystrix brachyura) In Captivity Deer Park Village Lamtanjong District Of Aceh And Village Panton Luas South Aceh Regency - Mira Salviana; Abdullah Abdullah; Mimie Saputri (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Malayan Porcupine is one of the protected wildlife in Indonesia. This animal has many benefits for humans. But the population continues to decline due to poaching. One way to save is with the conservation of these animals. Captive of Deer Park Village Lamtanjong is one conservation area in Aceh. This research was conducted in August until September 2016. The purpose of research was to determine the condition of the habitat Malayan Porcupine. The object of research is two tailed Malayan Porcupine, each of which is located in the village of Deer Park Breeding Lamtanjong Aceh Besar district and the village of Panton Luas South Aceh.  Data about the condition of the habitat is done by direct measurements during the research. Based on the research data is the average temperature during the research in Captive Deer Park Village Lamtanjong 28˚C (morning), 30,5˚C (noon), and 32,5˚C (afternoon),  While the temperature in the village of Panton Luas is at 24˚C (morning), 30˚C (noon), and 31,3˚C (afternoon).  Data humidity Captive Deer Park Village Lamtanjong was 44% (morning), 28% (noon), and 20% (afternoon), while the average humidity in the village of Panton Luas is 46.3 % (morning), 29% (noon), and 24% (afternoon).  Data measuring soil pH is 3,6 to Captive deer park Lamtanjong village, and 4.5 for the village of Panton Luas. Extensive data Breeding cage Malayan Porcupine in Deer Park is 3.15 m2 with a height of 2.3 meters, and 1.5 m2 with a height of 60 cm for Hedgehog in the village of Panton Luas. The conclusion of this research is the breeding habitat conditions in Deer Park and in the village of Panton Luas already support for the maintenance of a Porcupine.